Transcriptional regulation of human inducible nitric oxide synthase (NOS2) gene by cytokines: initial analysis of the human NOS2 promoter. - de Vera, M E (1996)
The expression of inducible nitric oxide synthase (NOS2) is complex and is regulated in part by gene transcription. In this investigation we studied the regulation of NOS2 in a human liver epithelial cell line (AKN-1) which expresses high levels of NOS2 mRNA and protein in response to tumor necrosis factor alpha, interleukin 1 beta, and interferon gamma (cytokine mix, CM). Nuclear run-on analysis revealed that CM transcriptionally activated the human NOS2 gene. To delineate the cytokine-responsive regions of the human NOS2 promoter, we stimulated AKN-1 cells with CM following transfection of NOS2 luciferase constructs. Analysis of the first 3.8 kb upstream of the NOS2 gene demonstrated basal promoter activity but failed to show any cytokine-inducible activity. However, 3- to 5-fold inductions of luciferase activity were seen in constructs extending up to -5.8 and -7.0 kg, and a 10-fold increase was seen upon transfection of a -16 kb construct. Further analysis of various NOS2 luciferase constructs ligated upstream of the thymidine kinase promoter identified three regions containing cytokine-responsive elements in the human NOS2 gene: -3.8 to -5.8, -5.8 to -7.0, and -7.0 to -16 kb. These results are in marked contrast with the murine macrophage NOS2 promoter in which only 1 kb of the proximal 5' flanking region is necessary to confer inducibility to lipopolysaccharide and interferon gamma. These data demonstrate that the human NOS2 gene is transcriptionally regulated by cytokines and identify multiple cytokine-responsive regions in the 5' flanking region of the human NOS2 gene.